CoB material, preparation method thereof and application of CoB material in photocatalytic CO2 cycloaddition

By adding NaBH4 to ZIF-67 material and pyrolyzed to prepare CoB material, the problem of high pressure and temperature required for photocatalytic chemical fixation of carbon dioxide in the prior art is solved, and a highly efficient catalytic cycloaddition reaction under low concentrations of CO2 is achieved. Improves the utilization efficiency and catalytic performance of light.

CN119386873APending Publication Date: 2025-02-07ZHEJIANG SCI-TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411357441.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The prior art requires high pressure and temperature in photocatalytic chemical fixation of carbon dioxide, high energy consumption, and MOFs materials may be inactivated under high temperature, high pressure or long-term use, and the stability and catalytic efficiency have not yet reached the ideal state.

Method used

CoB materials are prepared by pyrolysis using ZIF-67 as a template, and catalyzing the cycloaddition reaction of CO2 and epoxide under visible light, using the chemisorption of B elements that lack electrons and the combination of light to promote photogenesis of electrons-space The separation of hole pairs and charge transfer improve catalytic activity.

Benefits of technology

It realizes efficient catalytic cycloaddition reaction under low concentration CO2 conditions, improves the utilization efficiency and catalytic performance of light, reduces energy consumption, and improves the stability and active sites of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386873A_ABST
    Figure CN119386873A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of nano material preparation and application, and provides a CoB material, a preparation method thereof and application of the CoB material in photocatalytic CO2 cycloaddition. The preparation method comprises the following steps: grinding a ZIF-67 material and NaBH4 to obtain a mixture; and pyrolyzing the obtained mixture in an inert atmosphere, washing a product obtained by pyrolyzing, filtering and drying to obtain the CoB material. The obtained CoB material has ultrahigh specific surface area, more active sites and excellent photothermal conversion performance, the existence of the B element has a chemical adsorption effect on CO2, and the combination of boron and light has a promotion effect on a CO2 cycloaddition reaction, so that the utilization efficiency of light can be greatly improved, the catalytic performance can be improved, and the application prospect is wide. And the photocatalyst has excellent catalytic performance in photocatalytic CO2 and epoxide cycloaddition reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nano material preparation and application, and in particular to a CoB material and a preparation method thereof and application in photocatalytic CO2 cycloaddition. Background Art

[0002] With the increase in carbon dioxide emissions, environmental and ecological problems have become increasingly prominent, and the development of carbon dioxide fixation technology and emission reduction issues have attracted much attention. Among them, photocatalytic chemical fixation of carbon dioxide is a promising fixation method due to its mild conditions, environmental friendliness, diverse products, and high yield. By reacting carbon dioxide with epichlorohydrin to form cyclic carbonates, carbon dioxide can be captured and utilized, reducing atmospheric emissions and helping to address climate change. Cyclic carbonates can be used as an effective way to utilize carbon resources and have potential biomedical applications. However, the reaction requires high pressure and temperature, and has high energy consumption, so the development of efficient catalysts is urgently needed.

[0003] MOFs (metal organic frameworks) are a class of crystalline materials composed of metal ions or clusters connected to organic ligands through coordination bonds. They have highly ordered pore structures and controllable chemical properties, and have broad application prospects in gas storage, separation, catalysis and other fields. However, some MOFs materials may be deactivated under high temperature, high pressure or long-term use, and their stability remains to be solved. The synthesis process is complex, requiring precise conditions and long-term reactions, which increases costs and cycles. Although MOFs have good catalytic performance, their catalytic efficiency still needs to be improved relative to traditional catalysts. In some cases, the selectivity of MOFs materials is insufficiently controlled, resulting in uneven product distribution or side reactions. Therefore, we need to develop more functionalization strategies to improve the catalytic activity of MOFs for the cycloaddition of epoxides and CO2.

[0004] For example, Zhao et al. [Zhao X, Zhou Y, Huang K, et al. Ultralow loading cobalt-based nanocatalyst for benign and efficient aerobic oxidation of allylicalcohols and biobased olefins [J]. ACS Sustainable Chemistry & Engineering, 2018, 7 (2): 1901-1908.] encapsulated Co(acac)2 into the pores of ZIF-8 in situ to prepare Co(acac)2@ZIF-8 composite materials, which were then pyrolyzed and converted into Co x / NC catalysts for efficient aerobic oxidation of allyl alcohol and bio-based olefins. Summary of the invention

[0005] In order to overcome at least one of the shortcomings and deficiencies of the above-mentioned prior art, the present invention aims to develop a method for preparing a CoB material by pyrolysis using ZIF-67 as a template and its application in visible light catalytic CO2 cycloaddition. The present invention achieves efficient catalytic cycloaddition reaction under low CO2 concentration conditions by constructing multi-level porous MOFs doped with heteroatoms. There is a strong interaction between electron-deficient B and the lone oxygen pair in CO2, so the presence of B element has a chemical adsorption effect on CO2, and the combination of boron and light has a promoting effect on the CO2 cycloaddition reaction. The incorporation of B expands the light absorption range of the material, promotes the separation ability of photogenerated electron-hole pairs, and improves the charge transfer efficiency; it can also act as a Lewis acid site to activate epoxides. The adsorption of B on CO2 and its combination with light, the mutual synergy of Lewis acid, Lewis base active sites and MOFs multi-level pores, can achieve efficient light synergistic catalytic CO2 and epoxide cycloaddition to prepare cyclic carbonates.

[0006] The technical solution of the present invention is as follows:

[0007] A first aspect of the present invention provides a method for preparing a CoB material, comprising the following steps:

[0008] The ZIF-67 material and NaBH4 are fully ground to obtain a mixture;

[0009] The obtained mixture is placed in an inert atmosphere for pyrolysis, and the pyrolysis product is washed, filtered and dried to obtain a CoB material.

[0010] Preferably, the mass ratio of the ZIF-67 material to NaBH4 is 3:6-14; preferably, the mass ratio of the ZIF-67 material to NaBH4 is 3:8-12; more preferably, it is 3:9-11.

[0011] Preferably, the grinding time is 5 to 15 minutes.

[0012] Preferably, the pyrolysis temperature is 500-1000° C., and the pyrolysis time is 1-4 hours.

[0013] Preferably, the drying is vacuum drying, the vacuum drying temperature is 60-100° C., the vacuum drying time is 6-18 h, and the heating rate is 3-7° C. / min.

[0014] Preferably, the preparation method of the ZIF-67 material comprises the following steps:

[0015] Add Co(NO3)2·6H2O into the solvent and dissolve it by ultrasonic to obtain a metal salt solution;

[0016] 2-Methylimidazole is added into a solvent and dissolved by ultrasonication to obtain an organic ligand solution;

[0017] The metal salt solution and the organic ligand solution are mixed, stirred evenly, and allowed to stand for reaction at 25-35° C. for a period of time. After the reaction, the solid product is separated by centrifugation, washed, and dried to obtain the ZIF-67 material.

[0018] Preferably, in the preparation method of the ZIF-67 material:

[0019] The molar concentration of Co(NO3)2·6H2O in the metal salt solution is 0.02-0.05 mol / L;

[0020] The molar concentration of 2-methylimidazole in the organic ligand solution is 0.1 to 0.5 mol / L;

[0021] The organic ligand and the metal salt are dissolved in the solvent by ultrasound, and the ultrasound time is 5 to 30 minutes;

[0022] The solvent was anhydrous methanol.

[0023] Preferably, in the preparation method of the ZIF-67 material:

[0024] The static reaction time is 12 to 36 hours;

[0025] The drying is vacuum drying, the vacuum drying temperature is 60-100° C., and the vacuum drying time is 6-18 hours.

[0026] A second aspect of the present invention provides a CoB material, which is prepared by the preparation method described in one of the above.

[0027] The third aspect of the present invention provides the use of the above-mentioned CoB material in the photocatalytic cycloaddition reaction of CO2 and epoxide at room temperature.

[0028] Preferably, the application method is: mixing the obtained CoB material with an epichlorohydrin solution, introducing CO2, and performing a cycloaddition reaction under light.

[0029] The present invention has at least one of the following beneficial effects:

[0030] 1. The preparation method of the present invention is simple and quick to operate, green and environmentally friendly, and low in cost.

[0031] 2. The present invention prepares CoB material by directly pyrolyzing a mixture synthesized by grinding ZIF-67 and NaBH4. The material has an ultra-high specific surface area and a large number of active sites. It can undergo a CO2 and epoxide ring addition reaction under light irradiation conditions and has a high energy conversion efficiency. The CoB material obtained by the present invention has excellent photothermal conversion performance, can greatly improve the utilization efficiency of light and improve the catalytic performance.

[0032] 3. The CoB material prepared by the present invention has excellent catalytic performance in the photocatalytic CO2 and epoxide cycloaddition reaction, strong applicability, and good practical application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is the XRD pattern of the CoB material obtained in Example 3;

[0034] Figure 2 This is a performance diagram of the CoB material obtained in Example 3 in catalyzing the cycloaddition reaction of CO2 and epoxide under visible light. DETAILED DESCRIPTION

[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Example 1

[0037] In this embodiment, the CoB material is prepared by directly pyrolyzing the mixture obtained by grinding ZIF-67 and NaBH4 and applied in the photocatalytic CO2 cycloaddition reaction:

[0038] (1) Co(NO3)2·6H2O (2.33 g) was added to anhydrous methanol (200 mL) and dissolved by ultrasonication for 10 min to obtain a metal salt solution A; 2-methylimidazole (5.28 g) was added to anhydrous methanol (200 mL) and dissolved by ultrasonication for 10 min to obtain an organic ligand solution B;

[0039] (2) adding the organic ligand solution B obtained in step (1) to the metal salt solution A and mixing them, stirring for ten minutes to mix evenly, standing at 30° C. for 24 hours, cooling, centrifuging, washing with anhydrous methanol, and vacuum drying at 70° C. for 12 hours to obtain ZIF-67 material;

[0040] (3) Weigh the ZIF-67 material (150 mg) obtained in step (2) and NaBH4 (300 mg), add them into a mortar and grind for 10 min to obtain a mixture;

[0041] (4) Weigh the mixture obtained in step (3) (100 mg), send it into a tube furnace for pyrolysis under argon atmosphere, the heating rate is 5 ° C / min, and the temperature is kept at 900 ° C for 1 hour. After cooling to room temperature, take it out, wash the pyrolysis product with deionized water, filter and dry the obtained 1#CoB material, which can be used directly;

[0042] (5) Weigh the 1#CoB material (10 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), dissolve them in N,N-dimethylformamide (2 mL), introduce CO2, and carry out a cycloaddition reaction under light.

[0043] Example 2

[0044] In this embodiment, the CoB material is prepared by directly pyrolyzing the mixture obtained by grinding ZIF-67 and NaBH4 and applied in the photocatalytic CO2 cycloaddition reaction:

[0045] (1) Co(NO3)2·6H2O (2.33 g) was added to anhydrous methanol (200 mL) and dissolved by ultrasonication for 10 min to obtain a metal salt solution A; 2-methylimidazole (5.28 g) was added to anhydrous methanol (200 mL) and dissolved by ultrasonication for 10 min to obtain an organic ligand solution B;

[0046] (2) adding the organic ligand solution B obtained in step (1) to the metal salt solution A and mixing them, stirring for ten minutes to mix evenly, standing at 30° C. for 24 hours, cooling, centrifuging, washing with anhydrous methanol, and vacuum drying at 70° C. for 12 hours to obtain ZIF-67 material;

[0047] (3) Weigh the ZIF-67 material (150 mg) obtained in step (2) and NaBH4 (400 mg), add them into a mortar and grind for 10 min to obtain a mixture;

[0048] (4) Weigh the mixture obtained in step (3) (100 mg), send it into a tube furnace for pyrolysis under argon atmosphere, the heating rate is 5 ° C / min, and the temperature is kept at 900 ° C for 1 hour. After cooling to room temperature, take it out, wash the pyrolysis product with deionized water, filter and dry the obtained 2#CoB material, which can be used directly;

[0049] (5) Weigh the 2#CoB material (10 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.

[0050] Example 3

[0051] In this embodiment, the CoB material is prepared by directly pyrolyzing the mixture obtained by grinding ZIF-67 and NaBH4 and applied in the photocatalytic CO2 cycloaddition reaction:

[0052] (1) Co(NO3)2·6H2O (2.33 g) was added to anhydrous methanol (200 mL) and dissolved by ultrasonication for 10 min to obtain a metal salt solution A; 2-methylimidazole (5.28 g) was added to anhydrous methanol (200 mL) and dissolved by ultrasonication for 10 min to obtain an organic ligand solution B;

[0053] (2) adding the organic ligand solution B obtained in step (1) to the metal salt solution A and mixing them, stirring for ten minutes to mix evenly, standing at 30° C. for 24 hours, cooling, centrifuging, washing with anhydrous methanol, and vacuum drying at 70° C. for 12 hours to obtain ZIF-67 material;

[0054] (3) Weigh the ZIF-67 material (150 mg) obtained in step (2) and NaBH4 (500 mg), add them into a mortar and grind for 10 min to obtain a mixture;

[0055] (4) Weigh the mixture obtained in step (3) (100 mg), send it into a tube furnace for pyrolysis under argon atmosphere, the heating rate is 5 ° C / min, and the temperature is kept at 900 ° C for 1 hour. After cooling to room temperature, take it out, wash the pyrolysis product with deionized water, filter and dry the obtained 3#CoB material, which can be used directly;

[0056] (5) Weigh the 3#CoB material (10 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.

[0057] Example 4

[0058] In this embodiment, the CoB material is prepared by directly pyrolyzing the mixture obtained by grinding ZIF-67 and NaBH4 and applied in the photocatalytic CO2 cycloaddition reaction:

[0059] (1) Co(NO3)2·6H2O (2.33 g) was added to anhydrous methanol (200 mL) and dissolved by ultrasonication for 10 min to obtain a metal salt solution A; 2-methylimidazole (5.28 g) was added to anhydrous methanol (200 mL) and dissolved by ultrasonication for 10 min to obtain an organic ligand solution B;

[0060] (2) adding the organic ligand solution B obtained in step (1) to the metal salt solution A and mixing them, stirring for ten minutes to mix evenly, standing at 30° C. for 24 hours, cooling, centrifuging, washing with anhydrous methanol, and vacuum drying at 70° C. for 12 hours to obtain ZIF-67 material;

[0061] (3) Weigh the ZIF-67 material (150 mg) obtained in step (2) and NaBH4 (600 mg), add them into a mortar and grind for 10 min to obtain a mixture;

[0062] (4) Weigh the mixture obtained in step (3) (100 mg), send it into a tube furnace for pyrolysis under argon atmosphere, the heating rate is 5 ° C / min, and the temperature is kept at 900 ° C for 1 hour. After cooling to room temperature, take it out, wash the pyrolysis product with deionized water, filter and dry the obtained 4#CoB material, which can be used directly;

[0063] (5) Weigh the 4#CoB material (10 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.

[0064] Example 5

[0065] In this embodiment, the CoB material is prepared by directly pyrolyzing the mixture obtained by grinding ZIF-67 and NaBH4 and applied in the photocatalytic CO2 cycloaddition reaction:

[0066] (1) Co(NO3)2·6H2O (2.33 g) was added to anhydrous methanol (200 mL) and dissolved by ultrasonication for 10 min to obtain a metal salt solution A; 2-methylimidazole (5.28 g) was added to anhydrous methanol (200 mL) and dissolved by ultrasonication for 10 min to obtain an organic ligand solution B;

[0067] (2) adding the organic ligand solution B obtained in step (1) to the metal salt solution A and mixing them, stirring for ten minutes to mix evenly, standing at 30° C. for 24 hours, cooling, centrifuging, washing with anhydrous methanol, and vacuum drying at 70° C. for 12 hours to obtain ZIF-67 material;

[0068] (3) Weigh the ZIF-67 material (150 mg) obtained in step (2) and NaBH4 (700 mg), add them into a mortar and grind for 10 min to obtain a mixture;

[0069] (4) Weigh the mixture obtained in step (3) (100 mg), send it into a tube furnace for pyrolysis under argon atmosphere, the heating rate is 5 ° C / min, and the temperature is kept at 900 ° C for 1 hour. After cooling to room temperature, take it out, wash the pyrolysis product with deionized water, filter and dry the obtained 5#CoB material, which can be used directly;

[0070] (5) Weigh the 5#CoB material (10 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.

[0071] Example 6

[0072] In this embodiment, the CoB material is prepared by directly pyrolyzing the mixture obtained by grinding ZIF-67 and NaBH4 and applied in the photocatalytic CO2 cycloaddition reaction:

[0073] (1) Co(NO3)2·6H2O (2.33 g) was added to anhydrous methanol (200 mL) and dissolved by ultrasonication for 10 min to obtain a metal salt solution A; 2-methylimidazole (5.28 g) was added to anhydrous methanol (200 mL) and dissolved by ultrasonication for 10 min to obtain an organic ligand solution B;

[0074] (2) adding the organic ligand solution B obtained in step (1) to the metal salt solution A and mixing them, stirring for ten minutes to mix evenly, standing at 30° C. for 24 hours, cooling, centrifuging, washing with anhydrous methanol, and vacuum drying at 70° C. for 12 hours to obtain ZIF-67 material;

[0075] (3) Weigh the ZIF-67 material (150 mg) obtained in step (2) and NaBH4 (500 mg), add them into a mortar and grind for 10 min to obtain a mixture;

[0076] (4) Weigh the mixture obtained in step (3) (100 mg), send it into a tube furnace for pyrolysis under argon atmosphere, the heating rate is 5 ° C / min, and the temperature is kept at 700 ° C for 1 hour. After cooling to room temperature, take it out, wash the pyrolysis product with deionized water, filter and dry the obtained 6#CoB material, which can be used directly;

[0077] (5) Weigh the 6#CoB material (10 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.

[0078] Example 7

[0079] In this embodiment, the CoB material is prepared by directly pyrolyzing the mixture obtained by grinding ZIF-67 and NaBH4 and applied in the photocatalytic CO2 cycloaddition reaction:

[0080] (1) Co(NO3)2·6H2O (2.33 g) was added to anhydrous methanol (200 mL) and dissolved by ultrasonication for 10 min to obtain a metal salt solution A; 2-methylimidazole (5.28 g) was added to anhydrous methanol (200 mL) and dissolved by ultrasonication for 10 min to obtain an organic ligand solution B;

[0081] (2) adding the organic ligand solution B obtained in step (1) to the metal salt solution A and mixing them, stirring for ten minutes to mix evenly, standing at 30° C. for 24 hours, cooling, centrifuging, washing with anhydrous methanol, and vacuum drying at 70° C. for 12 hours to obtain ZIF-67 material;

[0082] (3) Weigh the ZIF-67 material (150 mg) obtained in step (2) and NaBH4 (500 mg), add them into a mortar and grind for 10 min to obtain a mixture;

[0083] (4) Weigh the mixture obtained in step (3) (100 mg), send it into a tube furnace for pyrolysis under argon atmosphere, the heating rate is 5 ° C / min, and the temperature is kept at 800 ° C for 1 hour. After cooling to room temperature, take it out, wash the pyrolysis product with deionized water, filter and dry the obtained 7#CoB material, which can be used directly;

[0084] (5) Weigh the 7#CoB material (10 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.

[0085] Example 8

[0086] In this embodiment, the CoB material is prepared by directly pyrolyzing the mixture obtained by grinding ZIF-67 and NaBH4 and applied in the photocatalytic CO2 cycloaddition reaction:

[0087] (1) Co(NO3)2·6H2O (2.33 g) was added to anhydrous methanol (200 mL) and dissolved by ultrasonication for 10 min to obtain a metal salt solution A; 2-methylimidazole (5.28 g) was added to anhydrous methanol (200 mL) and dissolved by ultrasonication for 10 min to obtain an organic ligand solution B;

[0088] (2) adding the organic ligand solution B obtained in step (1) to the metal salt solution A and mixing them, stirring for ten minutes to mix evenly, standing at 30° C. for 24 hours, cooling, centrifuging, washing with anhydrous methanol, and vacuum drying at 70° C. for 12 hours to obtain ZIF-67 material;

[0089] (3) Weigh the ZIF-67 material (150 mg) obtained in step (2) and NaBH4 (500 mg), add them into a mortar and grind for 10 min to obtain a mixture;

[0090] (4) Weigh the mixture obtained in step (3) (100 mg), send it into a tube furnace for pyrolysis under argon atmosphere, the heating rate is 5 ° C / min, and the temperature is kept at 1000 ° C for 1 hour. After cooling to room temperature, take it out, wash the pyrolysis product with deionized water, filter and dry the obtained 8#CoB material, which can be used directly;

[0091] (5) Weigh the 8#CoB material (10 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.

[0092] Comparative Example 1 (NaBH4 is not added in step 3)

[0093] This comparative example provides a method for preparing a ZIF-67-900 material, comprising the following steps:

[0094] (1) Co(NO3)2·6H2O (2.33 g) was added to anhydrous methanol (200 mL) and dissolved by ultrasonication for 10 min to obtain a metal salt solution A; 2-methylimidazole (5.28 g) was added to anhydrous methanol (200 mL) and dissolved by ultrasonication for 10 min to obtain an organic ligand solution B;

[0095] (2) adding the organic ligand solution B obtained in step (1) to the metal salt solution A and mixing them, stirring for ten minutes to mix evenly, standing at 30° C. for 24 hours, cooling, centrifuging, washing with anhydrous methanol, and vacuum drying at 70° C. for 12 hours to obtain ZIF-67 material;

[0096] (3) Weigh the ZIF-67 material (100 mg) obtained in step (2), put it into a tube furnace for pyrolysis under argon atmosphere, with a heating rate of 5°C / min and a constant temperature of 900°C for 1 h. After cooling to room temperature, take it out to obtain the ZIF-67-900 material which can be used directly;

[0097] (4) Weigh the ZIF-67-900 composite material (10 mg) obtained in step (3), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.

[0098] Comparative Example 2 (no grinding in step 3)

[0099] In this comparative example, the CoB material is prepared by directly pyrolyzing the mixture of ZIF-67 and NaBH4 and applying it in the photocatalytic CO2 cycloaddition reaction:

[0100] (1) Co(NO3)2·6H2O (2.33 g) was added to anhydrous methanol (200 mL) and dissolved by ultrasonication for 10 min to obtain a metal salt solution A; 2-methylimidazole (5.28 g) was added to anhydrous methanol (200 mL) and dissolved by ultrasonication for 10 min to obtain an organic ligand solution B;

[0101] (2) adding the organic ligand solution B obtained in step (1) to the metal salt solution A and mixing them, stirring for ten minutes to mix evenly, standing at 30° C. for 24 hours, cooling, centrifuging, washing with anhydrous methanol, and vacuum drying at 70° C. for 12 hours to obtain ZIF-67 material;

[0102] (3) Weigh the ZIF-67 material (150 mg) obtained in step (2) and directly mix it with NaBH4 (500 mg) to obtain a mixture;

[0103] (4) Weigh the mixture obtained in step (3) (100 mg), put it into a tube furnace for pyrolysis under argon atmosphere, the heating rate is 5 ° C / min, and the temperature is kept at 900 ° C for 1 hour. After cooling to room temperature, take it out, wash the pyrolysis product with deionized water, filter and dry the obtained CoB material, which can be used directly;

[0104] (5) Weigh the CoB material (10 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.

[0105] Comparative Example 3 (Insufficient Grinding in Step 3)

[0106] In this comparative example, CoB material was prepared by directly pyrolyzing a mixture of ZIF-67 and NaBH4 obtained by insufficient grinding and applied in a photocatalytic CO2 cycloaddition reaction:

[0107] (1) Co(NO3)2·6H2O (2.33 g) was added to anhydrous methanol (200 mL) and dissolved by ultrasonication for 10 min to obtain a metal salt solution A; 2-methylimidazole (5.28 g) was added to anhydrous methanol (200 mL) and dissolved by ultrasonication for 10 min to obtain an organic ligand solution B;

[0108] (2) adding the organic ligand solution B obtained in step (1) to the metal salt solution A and mixing them, stirring for ten minutes to mix evenly, standing at 30° C. for 24 hours, cooling, centrifuging, washing with anhydrous methanol, and vacuum drying at 70° C. for 12 hours to obtain ZIF-67 material;

[0109] (3) Weigh the ZIF-67 material (150 mg) obtained in step (2) and NaBH4 (500 mg), add them into a mortar and grind for 2 min to obtain a mixture;

[0110] (4) Weigh the mixture obtained in step (3) (100 mg), put it into a tube furnace for pyrolysis under argon atmosphere, the heating rate is 5 ° C / min, and the temperature is kept at 900 ° C for 1 hour. After cooling to room temperature, take it out, wash the pyrolysis product with deionized water, filter and dry the obtained CoB material, which can be used directly;

[0111] (5) Weigh the CoB material (10 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.

[0112] Comparative Example 4 (the mass of NaBH4 in step 3 is 200 mg)

[0113] In this comparative example, the CoB material is prepared by directly pyrolyzing the mixture obtained by grinding ZIF-67 and NaBH4 and applied in the photocatalytic CO2 cycloaddition reaction:

[0114] (1) Co(NO3)2·6H2O (2.33 g) was added to anhydrous methanol (200 mL) and dissolved by ultrasonication for 10 min to obtain a metal salt solution A; 2-methylimidazole (5.28 g) was added to anhydrous methanol (200 mL) and dissolved by ultrasonication for 10 min to obtain an organic ligand solution B;

[0115] (2) adding the organic ligand solution B obtained in step (1) to the metal salt solution A and mixing them, stirring for ten minutes to mix evenly, standing at 30° C. for 24 hours, cooling, centrifuging, washing with anhydrous methanol, and vacuum drying at 70° C. for 12 hours to obtain ZIF-67 material;

[0116] (3) Weigh the ZIF-67 material (150 mg) obtained in step (2) and NaBH4 (200 mg), add them into a mortar and grind for 10 min to obtain a mixture;

[0117] (4) Weigh the mixture obtained in step (3) (100 mg), put it into a tube furnace for pyrolysis under argon atmosphere, the heating rate is 5 ° C / min, and the temperature is kept at 900 ° C for 1 hour. After cooling to room temperature, take it out, wash the pyrolysis product with deionized water, filter and dry the obtained CoB material, which can be used directly;

[0118] (5) Weigh the CoB material (10 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.

[0119] Comparative Example 5 (the mass of NaBH4 in step 3 is 800 mg)

[0120] In this comparative example, the CoB material is prepared by directly pyrolyzing the mixture obtained by grinding ZIF-67 and NaBH4 and applied in the photocatalytic CO2 cycloaddition reaction:

[0121] (1) Co(NO3)2·6H2O (2.33 g) was added to anhydrous methanol (200 mL) and dissolved by ultrasonication for 10 min to obtain a metal salt solution A; 2-methylimidazole (5.28 g) was added to anhydrous methanol (200 mL) and dissolved by ultrasonication for 10 min to obtain an organic ligand solution B;

[0122] (2) adding the organic ligand solution B obtained in step (1) to the metal salt solution A and mixing them, stirring for ten minutes to mix evenly, standing at 30° C. for 24 hours, cooling, centrifuging, washing with anhydrous methanol, and vacuum drying at 70° C. for 12 hours to obtain ZIF-67 material;

[0123] (3) Weigh the ZIF-67 material (150 mg) obtained in step (2) and NaBH4 (800 mg), add them into a mortar and grind for 10 min to obtain a mixture;

[0124] (4) Weigh the mixture obtained in step (3) (100 mg), put it into a tube furnace for pyrolysis under argon atmosphere, the heating rate is 5 ° C / min, and the temperature is kept at 900 ° C for 1 hour. After cooling to room temperature, take it out, wash the pyrolysis product with deionized water, filter and dry the obtained CoB material, which can be used directly;

[0125] (5) Weigh the CoB material (10 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.

[0126] Comparative Example 6 (pyrolysis temperature in step 4 is 400°C)

[0127] In this comparative example, the CoB material is prepared by directly pyrolyzing the mixture obtained by grinding ZIF-67 and NaBH4 and applied in the photocatalytic CO2 cycloaddition reaction:

[0128] (1) Co(NO3)2·6H2O (2.33 g) was added to anhydrous methanol (200 mL) and dissolved by ultrasonication for 10 min to obtain a metal salt solution A; 2-methylimidazole (5.28 g) was added to anhydrous methanol (200 mL) and dissolved by ultrasonication for 10 min to obtain an organic ligand solution B;

[0129] (2) adding the organic ligand solution B obtained in step (1) to the metal salt solution A and mixing them, stirring for ten minutes to mix evenly, standing at 30° C. for 24 hours, cooling, centrifuging, washing with anhydrous methanol, and vacuum drying at 70° C. for 12 hours to obtain ZIF-67 material;

[0130] (3) Weigh the ZIF-67 material (150 mg) obtained in step (2) and NaBH4 (500 mg), add them into a mortar and grind for 10 min to obtain a mixture;

[0131] (4) Weigh the mixture obtained in step (3) (100 mg), put it into a tube furnace for pyrolysis under argon atmosphere, the heating rate is 5 ° C / min, and the temperature is kept at 400 ° C for 1 h. After cooling to room temperature, take it out, wash the pyrolysis product with deionized water, filter and dry the obtained CoB material, which can be used directly;

[0132] (5) Weigh the CoB material (10 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.

[0133] Comparative Example 7 (pyrolysis temperature in step 4 is 1100° C.)

[0134] In this comparative example, the CoB material is prepared by directly pyrolyzing the mixture obtained by grinding ZIF-67 and NaBH4 and applied in the photocatalytic CO2 cycloaddition reaction:

[0135] (1) Co(NO3)2·6H2O (2.33 g) was added to anhydrous methanol (200 mL) and dissolved by ultrasonication for 10 min to obtain a metal salt solution A; 2-methylimidazole (5.28 g) was added to anhydrous methanol (200 mL) and dissolved by ultrasonication for 10 min to obtain an organic ligand solution B;

[0136] (2) adding the organic ligand solution B obtained in step (1) to the metal salt solution A and mixing them, stirring for ten minutes to mix evenly, standing at 30° C. for 24 hours, cooling, centrifuging, washing with anhydrous methanol, and vacuum drying at 70° C. for 12 hours to obtain ZIF-67 material;

[0137] (3) Weigh the ZIF-67 material (150 mg) obtained in step (2) and NaBH4 (500 mg), add them into a mortar and grind for 10 min to obtain a mixture;

[0138] (4) Weigh the mixture obtained in step (3) (100 mg), put it into a tube furnace for pyrolysis under argon atmosphere, the heating rate is 5 ° C / min, and the temperature is kept at 1100 ° C for 1 hour. After cooling to room temperature, take it out, wash the pyrolysis product with deionized water, filter and dry the obtained CoB material, which can be used directly;

[0139] (5) Weigh the CoB material (10 mg) obtained in step (4), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under light.

[0140] The following tests were performed on the CoB materials and ZIF-67-900 materials obtained in Examples 1 to 8 and Comparative Examples 1 to 7:

[0141] (1) The powder diffraction (XRD) results of the 3#CoB material obtained in Example 3 are as follows: Figure 1 As shown, the characteristic peaks of 3#CoB are consistent with the standard card of CoB, indicating the successful synthesis of CoB material.

[0142] (2) Example 3 CoB material was prepared by directly pyrolyzing a mixture of ZIF-67 and NaBH4 and grinding and applied in a photocatalytic CO2 cycloaddition reaction. The performance test results of the material in catalyzing the cycloaddition reaction of CO2 and epoxide under visible light were as follows: Figure 2 As shown, the results show that the reaction performance of the material obtained by pyrolysis at a suitable temperature is significantly enhanced, and a conversion rate of 99% and a selectivity of 99% can be achieved within 3 hours, indicating that CoB materials can greatly improve the utilization efficiency of light and improve catalytic performance.

[0143] (3) The materials of Examples 1 to 8 and Comparative Examples 1 to 7 were used to catalyze the cycloaddition reaction of CO2 and epichlorohydrin to prepare propylene carbonate. The results are listed in Table 1.

[0144] Table 1

[0145]

[0146]

[0147] The experimental conditions for the catalytic reaction were as follows: catalyst (10 mg), epichlorohydrin (0.1 mmol), tetrabutylammonium bromide (0.1 mmol), N,N-dimethylformamide (2 mL), 300 mWcm -2 Full spectrum radiation, excess CO2, reaction time 3h.

[0148] From the data in Table 1, it can be seen that the CoB material prepared according to the present invention is an efficient CO2 and epichlorohydrin cycloaddition catalyst. Among them, the 3#CoB material obtained in Example 3 has the best catalytic effect ( Figure 2 ), a conversion rate of 99% and a selectivity of 99% (propylene chlorocarbonate) can be achieved within 3 h, indicating that B atom doping in CoB materials can significantly improve the catalytic activity.

[0149] Comparing Example 3 with Comparative Examples 1 to 7, it can be seen that the conversion rate of Example 3 is significantly higher than that of Comparative Examples 1 to 7, which indicates that whether NaBH4 is added, the amount of NaBH4 added, the grinding time and the pyrolysis temperature will affect the conversion rate.

[0150] In summary, the present invention adds NaBH4 to the ZIF-67 material and selects a suitable ratio, grinding time and pyrolysis temperature of the two, so that the CoB material prepared by the present invention has an ultra-high specific surface area and more active sites; the CoB material obtained by the preparation method of the present invention has excellent catalytic performance in the cycloaddition reaction of CO2 and epichlorohydrin, which not only provides an effective and sustainable method for the stable production of high-value-added chemicals from CO2, but also provides ideas for preparing heterogeneous MOFs-based catalysts that efficiently catalyze the cycloaddition reaction of CO2 and epoxides without catalysts.

[0151] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a CoB material, characterized in that: The following steps are involved: Grinding the ZIF-67 material with NaBH4 to obtain a mixture; The obtained mixture is placed in an inert atmosphere for pyrolysis, and the pyrolysis product is washed, filtered and dried to obtain a CoB material.

2. The method for preparing a CoB material according to claim 1, characterized in that: The mass ratio of the ZIF-67 material to NaBH4 is 3:6-14; the grinding time is 5-15 min.

3. The method for preparing a CoB material according to claim 1, characterized in that: The pyrolysis temperature is 500-1000° C., the pyrolysis time is 1-4 hours, and the pyrolysis heating rate is 3-7° C. / min.

4. The method for preparing a CoB material according to claim 1, characterized in that: The drying is vacuum drying, the vacuum drying temperature is 60-100° C., and the vacuum drying time is 6-18 hours.

5. The method for preparing a CoB material according to claim 1, characterized in that: The preparation method of the ZIF-67 material comprises the following steps: Add Co(NO3)2·6H2O into the solvent and dissolve it by ultrasonic to obtain a metal salt solution; 2-Methylimidazole is added into a solvent and dissolved by ultrasonication to obtain an organic ligand solution; The metal salt solution and the organic ligand solution are mixed, stirred evenly, and allowed to stand for reaction at 25-35° C. for a period of time. After the reaction, the solid product is separated by centrifugation, washed, and dried to obtain the ZIF-67 material.

6. The method for preparing a CoB material according to claim 5, characterized in that: In the preparation method of the ZIF-67 material: The molar concentration of Co(NO3)2·6H2O in the metal salt solution is 0.02-0.05 mol / L; The molar concentration of 2-methylimidazole in the organic ligand solution is 0.1 to 0.5 mol / L; The organic ligand and the metal salt are dissolved in the solvent by ultrasound, and the ultrasound time is 5 to 30 minutes; The solvent was anhydrous methanol.

7. The method for preparing a CoB material according to claim 5, characterized in that: In the preparation method of the ZIF-67 material: The static reaction time is 12 to 36 hours; The drying is vacuum drying, the vacuum drying temperature is 60-100° C., and the vacuum drying time is 6-18 hours.

8. A CoB material, characterized in that: The method is prepared according to any one of claims 1 to 7.

9. Use of the CoB material as claimed in claim 8 in the photocatalytic cycloaddition reaction of CO2 and epoxide at room temperature.